Carbon-nanotube-based RF components with multiple applications - Franck, P. (2014)
Owing to their extraordinary electronic properties, carbon nanotubes (CNTs), as a building block, promise superior performance and novel functionalities for microwave electronic components. This review presents some of the last results obtained in three different fields of this fast moving area - antennas, interconnects and sensors. Electromagnetic and analytical models are used to evaluate and optimize component performance. Synergy between fabrication and simulation techniques allows the practical design of bundled-CNTs-based components. Opportunities are discussed from the fabrication of CNT materials (PECVD, CVD) to their implementation in components and systems by specific technological processes (Photolithography, Flip-Chip, Inkjet printing, etc.). Actual performance of fabricated prototypes and expected improvement based on the CNTs implementation are presented.